GENDER STEREOTYPES IN CONTEMPORARY DISCOURSE: AN ANALYSIS OF LITERARY, MEDIA AND ONLINE TEXTS - KENJAYEVA, Adolat Asrorovna (The Lingua Spectrum, 2025)
In contemporary society, gender stereotypes remain a key issue in social communication. These stereotypes influence the formation of public consciousness, the distribution of roles within the family and professional spheres, and the behaviour of individuals. The linguistic expression of these stereotypes is evident in all types of text, including fiction, media, and social networking sites.